1997
DOI: 10.1063/1.120037
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-scale linewidth fluctuations caused by polymer aggregates in resist films

Abstract: Linewidth fluctuation in resist patterns is a serious problem in electron beam nanolithography. We have observed granular structures with a diameter of 20–30 nm in resist films, and have determined that these structures cause the linewidth fluctuations. The granules are made up of polymer aggregates. We discuss the origin of the aggregates from the result that their size depends on the polymer molecular weight. We also show that the linewidth fluctuation is reduced, though the developing rate is slow, when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
75
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 8 publications
1
75
1
Order By: Relevance
“…During the initial roughness formation (etch time from 0 seconds to 66 seconds), cone shaped roughness features appear and increase gradually in number on the surface [ Figure 1 (a-e)]. The roughness features show good uniformity in lateral size (~20 nm) and form, thus resembling the polymer aggregates observed in photoresist materials during development [25,[31][32][33]. Initial roughness formation is very different from the initial roughness induced by common ion bombardment or redeposition of sputtered materials from the chamber wall that normally leads to craters or clusters of random size and shape.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…During the initial roughness formation (etch time from 0 seconds to 66 seconds), cone shaped roughness features appear and increase gradually in number on the surface [ Figure 1 (a-e)]. The roughness features show good uniformity in lateral size (~20 nm) and form, thus resembling the polymer aggregates observed in photoresist materials during development [25,[31][32][33]. Initial roughness formation is very different from the initial roughness induced by common ion bombardment or redeposition of sputtered materials from the chamber wall that normally leads to craters or clusters of random size and shape.…”
Section: Resultsmentioning
confidence: 95%
“…There are two possible causes of aggregation. It may be induced intrinsically throughout the film during polymer sample preparation [31][32][33] or induced at the surface due to plasma exposure [21]. If polymer aggregation is intrinsic, the inhomogeneity could induce etch rate non-uniformity immediately upon plasma exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1(a) shows a schematic diagram of the LER generation process in a positive-tone resist. It has been confirmed that polymer aggregates are normally contained in resist films by observing cross-sections of resist films with a scanning electron microscope (SEM) [10] and also by observing the exposed resist surface after development with an atomic force microscope (AFM) [4,5,[10][11][12]. When such a resist film containing the polymer aggregates is developed after exposure, the developer molecules diffuse faster between aggregates and then the polymers surrounding the aggregates dissolve faster than the aggregates themselves.…”
Section: Introductionmentioning
confidence: 94%
“…This is because most LER are reported to have a magnitude of 3 nm or more [4][5][6][7][8][9] and the major cause is by polymer aggregates in resist films. The size of the polymer aggregates normally contained in resist films are 20 to 30 nm [4,10]. The polymer aggregates embedded on the pattern sidewall after development generate the LER [1 1,12].…”
Section: Introductionmentioning
confidence: 99%